2016
DOI: 10.1523/jneurosci.4131-14.2016
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Processing of Faces in the Human Brain Is Tuned to Typical Feature Locations

Abstract: Faces are salient social stimuli whose features attract a stereotypical pattern of fixations. The implications of this gaze behavior for perception and brain activity are largely unknown. Here, we characterize and quantify a retinotopic bias implied by typical gaze behavior toward faces, which leads to eyes and mouth appearing most often in the upper and lower visual field, respectively. We found that the adult human visual system is tuned to these contingencies. In two recognition experiments, recognition per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
72
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 66 publications
12
72
1
Order By: Relevance
“…Different types of objects tend to appear at different parts of the visual field and recent findings suggest that observers are attuned to these contingencies [30][31][32] . The most prominent spatial bias in the scene stimuli we used was a strong tendency for faces to appear in the upper visual field Supplementary Fig.…”
Section: Reliable Salience Biasesmentioning
confidence: 99%
“…Different types of objects tend to appear at different parts of the visual field and recent findings suggest that observers are attuned to these contingencies [30][31][32] . The most prominent spatial bias in the scene stimuli we used was a strong tendency for faces to appear in the upper visual field Supplementary Fig.…”
Section: Reliable Salience Biasesmentioning
confidence: 99%
“…The OFA might be a candidate for the cortical origin of these biases as well as for the development of detectors for diagnostic fragments. Patterns of responses in OFA (and neurons in the monkey putative homologue PL, Issa and DiCarlo, 2012) are tuned to typical locations of face fragments (Henriksson et al, 2015; de Haas et al, 2016). Population receptive fields of voxels in this region cover an area of the visual field that is large enough to integrate features of intermediate complexity at an average conversational distance (Kay et al, 2015; Grill-Spector et al, 2017b), such as combinations of eyes and eyebrows, which have been shown to be theoretically optimal and highly informative for object classification (Ullman et al, 2001, 2002; Ullman, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies have shown that face-processing areas such as OFA, pFus, and mFus have spatially restricted population receptive fields that could result in retinotopic differences (Kay et al, 2015; Silson et al, 2016; Grill-Spector et al, 2017b). In addition, local facial features activate the OFA (and the putative monkey homologue PL, see Issa and DiCarlo, 2012): responses to face parts are stronger when they are presented in typical locations (de Haas et al, 2016), and population activity in the OFA codes the position and relationship between face parts (Henriksson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for an increase of visual category information in the presence of realworld regularities has already been reported for individual object processing. Several studies showed that typical real-world positioning enhances the neural representation of object category (Chan et al, 2010;de Haas et al, 2016;: for example, neural responses to an airplane are better discriminable from responses to other objects when the airplane is shown in the upper visual field, where it is typically encountered in the real world. Does the presence of real-world structure similarly facilitate the representation of categorical scene content in scenes?…”
Section: Introductionmentioning
confidence: 99%